PENGARUH PENGETAHUAN AKUNTANSI, MOTIVASI KERJA, GOOD CORPORATE GOVERNANCE, DAN SKALA USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI: Studi Empiris Pada Perusahaan Spa di Kecamatan Kuta, Badung-Bali - Steffy Crystshoya Pondawa; Ni Nyoman Sri Rahayu Trisna Dewi (Journal Research of Accounting, 2020)
Tourism in Bali is currently developing very rapidly. In the midst of its development, the existence of the tourism sector needs to be supported by the availability of adequate accommodation such as hotels, restaurants, travel agents, spas and others to meet the needs of tourists. One of the accommodation facilities that is currently growing rapidly is the spa business. This study aims to determine the effect of accounting knowledge, work motivation, good corporate governance and business scale on the use of accounting information in spa companies in Kuta District, Badung-Bali. The population in this study is the owner / manager / cashier of the spa in Kuta District, amounting to 90 spa companies. In this study using a saturated sample, because all members of the population were sampled as many as 90 respondents consisting of spa owners / managers / cashiers in Kuta District. The data analysis technique used is multiple linear regression analysis. Based on the results of the analysis, it is known that accounting knowledge has a positive and significant effect on the use of accounting information in spa companies in Kuta District, Badung-Bali. Work motivation has a positive and significant effect on the use of accounting information in spa companies in Kuta District, Badung-Bali. Good corporate governance has a positive and significant effect on the use of accounting information on spa companies in Kuta District, Badung-Bali. Business scale does not affect the use of accounting information on spa companies in Kuta District, Badung-Bali.